Exploiting the Natural Diversity of RhlA Acyltransferases for the Synthesis of the Rhamnolipid Precursor 3-(3-Hydroxyalkanoyloxy)Alkanoic Acid - Germer, Andrea (Appl Environ Microbiol, 2020)
While rhamnolipids of the Pseudomonas aeruginosa type are commercially available, the natural diversity of rhamnolipids and their origin have barely been investigated. Here, we collected known and identified new rhlA genes encoding the acyltransferase responsible for the synthesis of the lipophilic rhamnolipid precursor 3-(3-hydroxyalkanoyloxy)alkanoic acid (HAA). Generally, all homologs were found in Betaproteobacteria and Gammaproteobacteria. A likely horizontal gene transfer event into Actinobacteria is the only identified exception. The phylogeny of the RhlA homologs from Pseudomonas and Burkholderia species is consistent with the organism phylogeny, and genes involved in rhamnolipid synthesis are located in operons. In contrast, RhlA homologs from the Enterobacterales do not follow the organisms’ phylogeny but form their own branch. Furthermore, in many Enterobacterales and Halomonas from the Oceanospirillales, an isolated rhlA homolog can be found in the genome. The RhlAs from Pseudomonas aeruginosa PA01, Pseudomonas fluorescens LMG 05825, Pantoea ananatis LMG 20103, Burkholderia plantarii PG1, Burkholderia ambifaria LMG 19182, Halomonas sp. strain R57-5, Dickeya dadantii Ech586, and Serratia plymuthica PRI-2C were expressed in Escherichia coli and tested for HAA production. Indeed, except for the Serratia RhlA, HAAs were produced with the engineered strains. A detailed analysis of the produced HAA congeners by high-performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS) highlights the congener specificity of the RhlA proteins. The congener length varies from 4 to 18 carbon atoms, with the main congeners consisting of different combinations of saturated or monounsaturated C(10), C(12), and C(14) fatty acids. The results are discussed in the context of the phylogeny of this unusual enzymatic activity. IMPORTANCE The RhlA specificity explains the observed differences in 3-(3-hydroxyalkanoyloxy)alkanoic acid (HAA) congeners. Whole-cell catalysts can now be designed for the synthesis of different congener mixtures of HAAs and rhamnolipids, thereby contributing to the envisaged synthesis of designer HAAs.